Fazer a práxis como fundamento metodológico para o ensino de Filosofia em Gramsci - SILVA, Fábio Soares da (2022)
Antonio Gramsci's philosophy of praxis, in the form of cordel literature, is the possibility of innovating our philosophy methodology in the classroom, offering more quality in the teaching practice of philosophy and favoring the learning of students at the State High School, Nazaré Ramos Teaching Center. The philosophy of praxis for Gramsci is constituted by the final action, which brings in its body the inseparability between theory and practice, in a process of understanding action, not purely practices, but theory grounded in the consciousness of action. According to Gramsci (1999), the concept of praxis takes another form, with different characteristics: praxis starts to be understood as history, as the making of history itself. It is, undeniably, the process that occurs with the interference of the human being in the conditions, mainly, in the school. Thus, the research object of this dissertation is the methodological praxis of philosophy teaching and the general objective is to present Gramsci's philosophy of praxis as a methodological proposal for the teaching of philosophy. The problematization that is presented is: how is it possible to present a methodological proposal for teaching philosophy from the philosophy of praxis in High School? The primary purpose of the problem in question is to propose a methodology for teaching philosophy as a philosophy of praxis and social emancipation aimed at transforming the praxis of philosophy teachers in high school, especially in the school field of research, resulting from the understanding of the philosophy of praxis. by Gramsci in the format of cordel literature. This research was developed through a qualitative study, of a bibliographic nature, involving action research, interviews, questionnaires and graphics, which allowed the researcher to intervene in the face of the problem. As a form of intervention, two thematic seminars were held to train philosophy professors and the students chosen for the research. The themes were: the philosophy of praxis and organic intellectuals in Gramsci and local politics from the philosophy of praxis. To produce the cordels, a philosophy workshop on cordel literature was held based on the philosophy of Gramscian praxis. The final product was made as a booklet of strings that were produced in the workshop by poets, professors, teachers and students. The results were analyzed through data from questionnaires, conversation circles with teachers and students. The analyzes showed that there were significant changes in the methodological practice of teachers and in the learning of students participating in the research.